Ethnic Ghettos and transcultural processes in a globalised city: new research on Harbin - Grüner, Frank; Prodöhl, Ines (Itinerario, 2011)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0165115312000046/resource/name/firstPage-S0165115312000046a.jpg